Landmark selection for route instructions: At which corner of an intersection is the preferred landmark located? - Hamburger, Kai; Röser, Florian; Knauff, Markus (Frontiers in Computer Science, 2022)
Cognitive studies showed that good landmarks – salient objects in the environment – make it easier for recipients of route instructions to find their way to the destination. Adding landmarks to route instructions also improves mobile navigation systems for pedestrians. But, which landmarks do people consider most helpful when giving route instructions? Four experiments explored this question. In the first experiment, the environment, including the route and landmarks, was presented on a map. The landmarks were located at the four corners of a right-angled intersection. Participants had to select those landmark-based route instructions they considered most helpful. In all other experiments, the environment was presented from an egocentric perspective, either in a video or as a sequence of pictures of intersections. Participants had to select those landmarks they would use in a route instruction. All landmarks had the same visual and semantic salience. The positions of the participants at the intersection were varied. Results show that participants consistently selected landmarks at the side of the road into which they had to turn. Moreover, the participants’ position at the intersection affected whether they selected landmarks before or behind the decision point. These results have consequences for human spatial cognition research and for the automatic selection of landmarks in mobile pedestrian navigation systems.